2019
DOI: 10.1007/s00344-019-09981-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Potassium Iodide and Iodosalicylates on the Antioxidant Potential and Iodine Accumulation in Young Tomato Plants

Abstract: Iodine (I) is classified as a beneficial element for plants. Until now, there have been only hypotheses regarding the uptakes of organic iodine compounds by plant roots. The purpose of our research was to compare the uptakes and effects of the application of the following mineral and organic iodine compounds on young tomato plants: KI, 5-iodosalicylic (5-ISA), and 3,5-diiodosalicylic (3,5-diISA) acids. An additional control combination included the treatment with salicylic acid (SA) alone. All compounds were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
2
15
0
1
Order By: Relevance
“…We found that the application of 5-ISA caused accumulation of a much higher content of iodine in plants than after KIO 3 and 3.5-diISA treatment. In a study conducted on tomato plants, the authors demonstrated that the absorption of iodine from the inorganic form (KI) is higher than iodine from iodosalicylates [63]. We showed that the application of iodosalicylates caused increased concentrations of these compounds in lettuce leaves.…”
Section: Discussionmentioning
confidence: 89%
“…We found that the application of 5-ISA caused accumulation of a much higher content of iodine in plants than after KIO 3 and 3.5-diISA treatment. In a study conducted on tomato plants, the authors demonstrated that the absorption of iodine from the inorganic form (KI) is higher than iodine from iodosalicylates [63]. We showed that the application of iodosalicylates caused increased concentrations of these compounds in lettuce leaves.…”
Section: Discussionmentioning
confidence: 89%
“…39 They also showed that the activity of POX in tomato leaves was dependent on the form and concentration of iodine. 39 A similar study was performed by Medrano-Macias et al, who also investigated antioxidant activity in tomato seedlings treated with iodide (I À ) and potassium iodate (IO 3 À ) at a dose of 1 mM daily and 100 mM twice per…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on tomato plants reported a 45% or 70% decrease in the biomass production by applying solid fertilizer containing 150 mg KI/kg soil (pH = 5.91, OM = 4.09%, total iodine = 2.02 mg/kg) [6] or irrigation water having 760 mg/L iodide concentration [15]. When the iodine concentration applied for biofortification was considerably reduced to 6.3 mg I − /L or 1-5 mM, it was found that the biomass production of edible parts did not change significantly as compared to the control plants [26,50]. The differences between our experimental and literature data can be explained by the fact that the applied iodine concentrations in our experiments were considerably lower, and the treatment technologies were also different.…”
Section: Discussionmentioning
confidence: 99%